Analizing Land Use Change and Direction for Controling Space Utilization at Industrial Area of Kasemen District, Serang City - Neni Sofiyanti; Santun R.P. Sitorus; Asep Denih (Jurnal Indonesia Sosial Teknologi, 2024)
The determination of industrial estates in Kasemen District has a significant influence on the area around the industrial area, especially on agricultural land, public green open spaces (RTH), and river borders around the industrial area. The methodology used in this study is the industrial location theory analysis method, the spatial analysis method of overlaying land use maps with spatial pattern maps of RTRW Serang City using QGis media, the method of analyzing the impact of determining industrial locations using leopod matrix, and the AHP SWOT method to analyze the direction of control. The location of the determination of industrial estates has been in accordance with the industrial location theory, changes in land use before and after the establishment of the RTRW regional regulation show a reduction in agricultural and fishery land, but the built-up land and mangrove forest land have increased and new land use has emerged including industrial land, service trade land. The identification of land use change occurred from 2009, 2016 to 2023. The results of the study show that the largest change in agricultural land use occurred in 2009 - 2016 of 833 hectares, while in 2016 - 2023 it was 90 hectares of land area in Kasemen District. This shows that after the establishment of the Serang City RTRW Regional Regulation, land changes in agricultural areas can be reduced to 0.01%.